Die Drogenproblematik im Strafvollzug Eine rechtliche und kriminologische Untersuchung - Bornefeld, Sven (Universitätsverlag Göttingen, 2023)
Drugs within detention facilities are a perennial issue. It will come as no surprise, that drugs are an inherent part of the subculture of captives. Despite of its relevance for the penal system, this issue is being neglected by the jurisprudential and criminological science. This publication wants to fill this gap of scientific assessment. The focus of this publication is the illustration of legal and practical countermeasures against drug issues and their practical limits in the detention facilities. At the same time it also consideres practical areas of tension concerning the goals of law enforcement. Furthermore the author has analysed miscellaneos empirical studies regarding the symptoms of drug addiction The focus of this publication is the illustration of legal and practical countermeasures against drug issues in the detention facilities, which occur in captives. For the purpose of his research, the author has also interviewed experts in the detention facilities of several federal states. The publication concluses with the presentation of the results of the author's own empirical study.